The Effect of Organizational Culture, Compensation, Job Satisfaction, And Work Environment on The Performance of Employees at Bank “Bantara” In the Jakarta Area - Mohamad Ramadhan Argakoesoemah; Rizky Nanda Verina (KALBISOCIO Jurnal Bisnis dan Komunikasi, 2026)
This research aims to analyse the performance of employees at Bank "Bantara" in the Jakarta Area by considering factors such as organizational culture, compensation, job satisfaction, and work environment. These factors were chosen as independent variables due to their potential impact on employee performance, which is the dependent variable. The researcher used the Statistical Structural Equation Modelling (SEM) method specifically the Partial Least Square (PLS) approach supported by SmartPLS, to process the data obtained from a questionnaire survey conducted online using Google Form. The results indicated that Organizational Culture and Work Environment have a positive and significant effect on Employee Performance, whereas Compensation and Job Satisfaction have a positive effect but not significant on Employee Performance.